The Effectiveness of Three Types of Tissue Culture Media on the Growth and Jasmone Content of Jasmine (Jasminum sambac) Callus: Efektivitas Tiga Jenis Media Kultur Jaringan Terhadap Pertumbuhan dan Kandungan Melati Kalus Melati (Jasminum sambac) - Widya, Surya Ari; Aritonang, Erfan Andrianto (Journal of Applied Plant Technology, 2024)
Jasmine is a herbaceous plant that has its own charm, especially its fragrant aroma, so the demand for jasmine extract is very popular. With the large industrial demand as a raw material, it is necessary to study the growth, development and content of jasmone in jasmine callus on 3 types of media in order to increase the content and efficiency of media use. This research aims to determine the growth, development and jasmone content in Jasminum sambac jasmine callus grown on MS (Murashige and Skoog), VW (vacin and Went), and NT (Nagata and Takebe) media in vitro. This research was carried out using a Completely Randomized Design (CRD), repeated 5 times and in each replication there were 3 samples. The treatment is as follows: 1. MS media (M1); 2. VW Media (M2); 3. Media NT(M3). Using parameters for observing the quantity and quality of callus by scoring once a week and analyzing secondary metabolites. From the results of observing the quantity, quality and analysis of secondary metabolites with modified treatment on MS, VW and NT media, it can be concluded that the quantity of callus is not significantly different, but the quantity of callus on NT (Nagata and Takebe) M3 media tended to be better than MS (Murashige and Skoog) M1 and VW (Vacin and Went) M2 media, while the results of callus quality from all media tended to be compact and the results of secondary metabolite content in the media treatment NT (Nagata and Takebe) M3 produced better jasmone content (1.22%) compared to MS (Murashige and Skoog) M1 and VW (Vacin and Went) M2 media.